Role of immune responses in the development of NAFLD-associated liver cancer and prospects for therapeutic modulation - Yahoo, Neda; Dudek, Michael; Knolle, Percy; Heikenwälder, Mathias (Journal of hepatology, 2023)
The liver is the central metabolic organ of the body, regulating energy and lipid metabolism, while also having potent immunological functions. Overwhelming the metabolic capacity of the liver via obesity and a sedentary lifestyle leads to hepatic lipid accumulation, chronic necro-inflammation, enhanced mitochondrial/endoplasmic reticulum stress and development of non-alcoholic fatty liver disease (NAFLD), and its more severe form non-alcoholic steatohepatitis (NASH). Based on an improved understanding of pathophysiological mechanisms, specifically targeting metabolic pathways to prevent or slow down the progression of NAFLD to liver cancer will become possible. Genetic/environmental factors are also known to contribute to the development of NASH and progression to liver cancer. The complex pathophysiology of NAFLD-NASH is reflected by environmental factors, particularly the gut microbiome and its metabolic products. NAFLD-associated HCC most often occurs in the context of a chronically inflamed and cirrhotic liver. Recognition of environmental alarmins or metabolites derived from the gut microbiota and the metabolically injured liver create a strong inflammatory milieu supported by innate and adaptive immunity. Several recent studies indicate that chronic steatosis induces auto-aggressive CD8+CXCR6+PD1+ T cells that eliminate parenchymal and non-parenchymal cells in an antigen-independent manner. This promotes chronic liver damage and a pro-tumorigenic environment. CD8+CXCR6+PD1+ T cells possess an exhausted, hyperactivated, resident phenotype; they trigger the NASH to HCC transition and might be responsible for weaker responses to immune checkpoint inhibitors - in particular atezolizumab/bevacizumab. Here, we provide an overview of NASH-related inflammation/pathogenesis, focusing on new discoveries on the role of T cells. This review discusses preventive measures to halt disease progression to liver cancer and therapeutic strategies to manage patients with NASH-HCC.